Obtaining Hydrogen and Carbon Materials from Hydrocarbonic Gas in Microwave Plasma Discharge at Amospheric Pressure - Zherlitsyn A. G. Aleksey Grirorievich (Materials Science and Technologies, 2015)
Title screen